Kamma Perspective in the Buddhist Philosophy - Panyatharo, Phrakrupalad Phoompha; Thantachitto, Phrakruwinaitorn Charoen; Wetprasit, Sunee (Journal of Dhamma for Life, 2022)
This academic article aims to study and present karma according to Buddhist philosophy. From the study, it was found that when there is intention, a person will perform karma by physical, verbal, and mental actions. Whether it’s a good or a bad way when someone has any karma will receive the result of that action which is in accordance with the law. That is, it is the law of cause and effect, that is, the law of action. Whatever karma (deed) you do, you will receive the result of your karma (action). It’s the law of justice. That is, always receiving the karma according to the cause of the action, which the nature of the mind tends to be inclined according to the power of defilements. Which reminds us of what is unwholesome more than what is charity. Therefore, we should diligently train our minds to think and think of only what is meritorious in order to prevent the mind from being miserable at every moment.